Contribution to the study of the solid-state reaction of mercury with pure rhodium - Milaré, E. [UNESP]; Fertonani, F. L. [UNESP]; Benedetti, Assis Vicente [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2000)
Thermogravimetry (TG) and other analysis techniques (EDX, SEM, Mapping surface, X-ray diffraction, inductively coupled argon plasma emission spectroscopy and atomic spectrometry with cold vapor generation) were used to study the reaction of Hg with Rh. The results permitted the suggestion that, when subjected to heat, an electrodeposited Hg film reacts with Rh to form intermetallic products with different stabilities, as indicated by at least three mass loss steps. In the first step, between room temperature and 160°C, only the bulk Hg is removed. From this temperature up to about 175°C, the mass loss can be attributed to the desorption of a film of metallic Hg. The last step, from 175 to 240°C, can be ascribed to the removal of Hg from a thin dark film of RhHg2.
Keywords: Atomic spectroscopy; Desorption; Electrodeposition; Emission spectroscopy; Energy dispersive spectroscopy; Heat treatment; Intermetallics; Rhodium; Scanning electron microscopy; Thermal effects; Thermogravimetric analysis; X ray diffraction analysis; Inductively coupled argon plasma emission spectroscopy; Solid state reaction; Mercury (metal)